A survey on healthcare professionals’ perspective on the use of benzoyl peroxide cleanser for acne management - Das, Anupam; Thangavel, Swetha; Sen, Dyotona; Jadhwar, Sameer (International Journal of Research in Dermatology, 2024)
Background: Acne vulgaris is a prevalent chronic dermatological condition affecting adolescents and young adults, with significant consequences on quality of life if left untreated. Effective management strategies are crucial to prevent scarring and psychological distress associated with acne. This study investigated the role of cleansers in acne management and explored healthcare professionals' perspectives and practices regarding acne treatment. Methods: An online questionnaire-based study, involving 126 healthcare professionals [HCPs (dermatologists and cosmetologists)] and 459 acne patients was conducted to assess patients’ acne severity, adherence to cleansing regimens, preferred cleansing agents, treatment duration, adjunctive therapies, and the impact of benzoyl peroxide 5% cleanser on acne control and patient satisfaction. Results: The majority of the patients presented with an IGA grade 3 (moderate) acne (48.59%) in the present survey. HCPs rated benzoyl peroxide as the most preferred cleansing agent for acne management in most of their patients (87.33%). Majority of the patients (41.53%) exhibited improvement within 15 days of using the benzoyl peroxide cleanser, highlighting its relatively rapid onset of action. The benzoyl peroxide treatment duration varied for patients, emphasizing the individualized nature of acne treatment. In most of the severe cases (39.87%), HCPs commonly supplemented benzoyl peroxide with topical retinoids, oral antibiotics, oral isotretinoin, or combination therapy. Conclusions: This study emphasizes the effectiveness and preference for benzoyl peroxide-based cleansers among HCPs and patients.